Using Morphological Characters to Support Decision-Making in Nature-Based Solutions: A Shortcut to Promote Urban Plant Biodiversity - Cíntia Luiza da Silva Luz; Ricardo Reale; Leticia Figueiredo Candido; Daniela Zappi; Giuliano Maselli Locosselli (Urban Science)
Cities are particularly vulnerable to climate change for their intrinsic characteristics. Imperviousness, heat islands, and pervasive pollution are common urban problems that challenge the current status quo in decision-making. As an alternative, Nature-based Solutions (NbS) arose from the need to tackle environmental issues through multifunctional solutions. Plant biodiversity is at the core of NbS, but such solutions are constrained by the limited knowledge of species benefits for cities, particularly in the biodiverse Global South. In this review, we stress the potential use of morphological characters from taxonomic studies as a shortcut to assess the ecosystem services of plant species. Species description and identification keys can be translated into ecosystem services to support the use of species not yet listed in cities. Bridging the potential for ecosystem service provision and morphological characters like life form, bark, leaf phenology and morphology, and reproductive morphology based on the comprehensive literature will allow decision-makers to widen their options to promote urban biodiversity. Building a platform requires summarizing plants’ ecosystem service knowledge and subsequently validating models’ predictive power. Still, this approach holds great potential to promote urban biodiversity for more resilient and enjoyable urban environments.